2022
DOI: 10.1002/pssa.202100480
|View full text |Cite
|
Sign up to set email alerts
|

CMOS Compatible Al‐Doped ZnO Sol–Gel Thin‐Film Properties

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/pssa.202100480.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…This control of the previously developed and studied thin lms will allow a better control of the nanowire growth parameters. 15,20 ZnO NWs have almost the same band gap with ZnO lm but a much larger thickness-surface area ratio compared to spincoating deposition. The results show that ZnO NWs have different morphologies, structures, and optical properties, proving that the buffer layer strongly inuences the growth and properties of ZnO nanostructures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This control of the previously developed and studied thin lms will allow a better control of the nanowire growth parameters. 15,20 ZnO NWs have almost the same band gap with ZnO lm but a much larger thickness-surface area ratio compared to spincoating deposition. The results show that ZnO NWs have different morphologies, structures, and optical properties, proving that the buffer layer strongly inuences the growth and properties of ZnO nanostructures.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Several low-cost deposition techniques have been investigated, and it has been found that many important parameters, such as precursor concentration, growth temperature, buffer layer type and thickness, affect the formation of ZnO. [15][16][17] The chemical bath deposition (CBD) technique has attracted the interest of the research community due to its simplicity, cost efficiency, low temperature and environmentally friendly growth deposition, as well as its ability to scale up to large areas for commercial production. 18,19 However, the relationships between the buffer layer and C-oriented NWs properties with preferential (002) planes are rather few addressed in the literature.…”
Section: Introductionmentioning
confidence: 99%